2018
DOI: 10.3390/su10082823
|View full text |Cite
|
Sign up to set email alerts
|

Does Institutional Context Affect CSR Disclosure? A Study on Eurostoxx 50

Abstract: Abstract:We propose to investigate the relationship between corporate social responsibility disclosure and institutional/environmental factors among a sample of European listed companies. We find that, by using several traditional explicative variables, institutional factors affect the level of CSR disclosure, in a context where the EU Commission has been paying growing attention to social and environmental accountability of listed companies (see the EU Dir. 95/2014). Our findings are further supported by mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 97 publications
5
61
0
2
Order By: Relevance
“…Similar results were found by Amor‐Esteban et al, (). Coluccia, Fontana, and Solimene () also found that social, political, and legal dimensions put forth important pressure on firms improving the transparency of corporate behavior especially on CSRD. We also extend the traditional agency theory‐based view to an organizational view by examining whether the impact of CG on CSED differs across legal regimes or remains stable.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…Similar results were found by Amor‐Esteban et al, (). Coluccia, Fontana, and Solimene () also found that social, political, and legal dimensions put forth important pressure on firms improving the transparency of corporate behavior especially on CSRD. We also extend the traditional agency theory‐based view to an organizational view by examining whether the impact of CG on CSED differs across legal regimes or remains stable.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%
“…According to Ortiz and Grado (2016), governance indicators of the World Bank, foreign direct investment significantly influences the corporate sustainability information of countries. Coluccia et al (2018) found that regulatory quality and rule of law were positively related to corporate social responsibility disclosures.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Corporate decisions to engage in sustainability reporting and responsible business operations could be limited by the institutional environment (Adnan et al, 2018;Coluccia, Fontana, & Solimene, 2018;Dagiliene & Nedzinskiene, 2018;Negash & Lemma, 2020). This study explores the relationship between the cumulative sustainability reporting practices of organizations in African countries over the past five years ending in 2017 and institutional factors (macroeconomic, political, and governance variables).…”
Section: Introductionmentioning
confidence: 99%
“…Lehmann and Benner [40] describe the theory and mechanism of the impact of region-specific institutional development on corporate behavior. Coluccia's [41] experimental conclusion shows that the external expansion behavior of SOEs is influenced by different institutional factors and external factors, such as supervision intensity, accounting system norms, external cultural influence, and the attitude of corporate stakeholders. These forces do have a systematic and coercive impact on a company's external expansion.…”
Section: H2b Government Intervention Has a Positive Mediation Effectmentioning
confidence: 99%
“…The firm size was measured by the total number of employees in local SOEs [16,18]. Second, the firm age in this paper was measured by the number of years since the local SOEs were founded [41]. Thirdly, we used a ratio of total debts to total assets to express leverage [11].…”
Section: For Details) Information Regarding Chinese Local Soes' Outwmentioning
confidence: 99%